2009
DOI: 10.1002/marc.200800623
|View full text |Cite
|
Sign up to set email alerts
|

Composite Polyamide 6/Polypyrrole Conductive Nanofibers

Abstract: Conductive Polyamide 6 (PA-6) nanofibers were prepared by making a conductive polypyrrole coating obtained by a polymerization of pyrrole molecules directly on the fiber surface. A solution of PA-6 added with ferric chloride in formic acid has been electrospun and the fibers obtained showed an average diameter of 260 nm with a smooth surface. The fibers have been then exposed to pyrrole vapours and a compact coating of polypyrrole was formed on the fiber surface. The growth of the coating was monitored by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
0
35
0
4
Order By: Relevance
“…Forciniti et al [54] suggested that blends of poly(lactic-co-glycolic acid) and chloride-doped PPy exhibit the same electrical properties that the individual CP. Conductive PPy coating polyamide 6 (PA6) nanofibers were prepared by polymerizing pyrrole monomers directly onto the fiber [55].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Forciniti et al [54] suggested that blends of poly(lactic-co-glycolic acid) and chloride-doped PPy exhibit the same electrical properties that the individual CP. Conductive PPy coating polyamide 6 (PA6) nanofibers were prepared by polymerizing pyrrole monomers directly onto the fiber [55].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Although this technique is rather easy to implement for most of synthetic polymers, the processing of conducting polymers is not straightforward, due to the relatively low solubility and the limited number of entanglements of these materials. A method to overcome this issue consists in the production of a polymer mat to act as template, where an in situ polymerization of monomers may occur [6,7]. This strategy has been exploited by Granato and co-workers [6] to obtain nanofibres with an insulating core and a conducting shell starting from a polyamide 6 (PA6) solution containing iron(III) chloride (FeCl3), which promotes the following polymerization of pyrrole vapours onto the fibre surface.…”
Section: Introductionmentioning
confidence: 99%
“…pyrrole, thiophene, aniline) to afford semiconducting and conducting polymers [14]. Such kind of oxidative polymerization of the aromatic monomers has been also demonstrated to occur in situ onto polymer films [15,16] and onto electrospun wire-shaped templates containing this oxidizing salt [6,17]. However, when polyamide is used as template, the effect of FeCl3 on the rheological properties of the polymer solution cannot be neglected, since the presence of the metal halide is known to strongly perturb or even prevent H-bonds formation between amide groups of polyamide backbones [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…3. Compared to the spectra of raw PA6 nanofibers, the absorption peaks of PA6 disappeared in the FTIR spectrum of PA6/ PPy core-shell nanofibers, such as the N-H and C-H stretching vibrations at 2800-3300 cm À 1 and the coupled motions of C ¼ O stretching and N-H in plane bending at 1500-1700 cm À 1 [28]. However, all characteristic absorption bands of PPy and the absorption bands are related to pyrrole ring stretching, C-N stretching vibration, C-H stretching vibration and C-H deformation appeared at 1547 cm À 1 , 1176 cm À 1 , 963 cm À 1 and 904 cm À 1 , respectively.…”
Section: Characterization Of Ppy Nanofibers Matmentioning
confidence: 86%